Fortalecimento das relações metropolitanas: o caso de São Paulo - Baines, Christian (2013)
This thesis' objective is to assess Brazilian policies in the area of TV content regulation in light of violation of human rights in TV programming, through a comparison with France and the United Kingdom. This is done through the analysis of the legal framework and the institutional mechanisms available to the different regulatory bodies in the three countries: the CSA in France, Ofcom in the UK and the Ministry of Communication in Brazil. The second part of this study analyses regulatory policies through case studies in which four types of human rights violations are encountered: prejudice and offence against minorities; women's rights violation; religious discrimination; and the trivialisation of violence and derogatory language. As a conclusion, recommendations towards a new regulatory policy for TV content are made, with the aim of prioritising and protecting human rights.